Educational Game Using Coordinate-Based Augmented Reality At Green Fresh Farm - Maximiliano, Oeij Dominic Aldrich; Widiantoro, Albertus Dwiyoga; Nugroho, Erdhi Widyarto (Journal of Business and Technology, 2024)
Tourist destinations in Indonesia are incredibly diverse. One of these destinations is Green Fresh Farm, located in the Gunungpati district, specifically in Jatirejo Village. Green Fresh Farm serves as a place for dairy cow farming and is also a tourist destination. Children visit this place for recreational purposes and to learn about cows.The creation of the MooLand AR game aims to determine whether the MooLand AR game is accepted as a means for introducing and educating about cattle farming at Green Fresh Farm. This includes educating visitors about cattle barn facilities, feeding techniques for dairy cattle, and educating about cattle diseases at Green Fresh Farm.    Based on the test results, the MooLand AR game is accepted as a means of introducing and educating visitors about cows at Green Fresh Farm. The analysis results indicate that the game correlates with ease of use, utility, and enjoyment, making MooLand AR successful and accepted as an educational game about cows at Green Fresh Farm.